TIME ANALYSIS USING EARNED VALUE METHOD ON PRESERVATION OF SECTION 5 PANDAAN TOLL EXIT ROAD IN MALANG - Amalia Fathimah Azh Zhahra Mughni; Hanie Teki Tjendani; Budi Witjaksana (Asosiasi Dosen Muda Indonesia, 2024)
The development of a country's road or toll road infrastructure can be used as a benchmark to judge a country's economic development at both macro and micro levels. The location of toll exits has a significant impact on labor absorption and the creation of new business activities. Projects are dynamic, so contractors must adapt to changing project situations and conditions if they are to succeed in achieving optimal profits. Today's highly competitive aspects of construction planning require high levels of accuracy, efficiency, effectiveness and economy in project analysis. In the world of construction projects, there is much that can be done, including controlling costs. In cost control, efforts can be made so that the realization of costs incurred is consistent with implementation needs and is not excessive, such as efforts to limit costs, that is, to realize savings without does not reduce quantity or quality. The earned value method is used to determine the project's performance in terms of cost at a certain time, determine the project's performance in terms of progress/time at a point in time. certain, estimate the cost to complete the project after the evaluation period and estimate the cost to complete the project after the evaluation period. Project completion time after evaluation. In this study, the author performed a cost analysis using the earned value method for the conservation of Pandaan Malang Section 5 toll road. The schedule variance value is Rp1,652,192,521 with the time performance index value of 1.139743112 or SPI value > 1, meaning this project has arrived at week 17, the implementation is faster than planned.The estimated project completion date or Expected Schedule (EAS) is 278 days, 22 days faster than the total contract period of 300 days.